A Medicolegal Autopsy for a Rabies Infection Case - Tuğcu, Harun; Dalgıç, Mustafa; Öngürü, Önder; Demirel, Birol; Celasun, Bülent (The Bulletin of Legal Medicine, 2003)
Rabies is an acute viral infectious disease with the highest mortality rate The causative agent is a neurotropic RNA virus in the family of Rhabdoviridae genus Lyssa virus. According to the records of Ministry of Health in Turkey; 529 people died from rabies between 1973-2001. It is estimated that human cases associated with rabies occur with an incidence of 25000 per year. Our case was a 21 years old male. He had a history of dog bite at the frontal site of his head and death occured within 25 days despite the prophylaxis. If a case is suspected to be dead because of infectious diseases, an autopsy can be performed without permission of relatives, by demand of officers, only. Spesific laboratory tests should also be done as a component of autopsy procedures in cases of human deaths associated with rabies. Autopsy team must be aware of the risk of transmission of virus and standard protocoles must be followed in disenfection of autopsy room, and instruments, and also in handling tissue samples. In this case, our purpose was to investigate and discuss the factors that may cause death in cases of rabies in spite of prophylaxis and highlight the biosafety considerations during autopsy in cases with suspicion of rabies.Key words: Rabies, autopsy, biosafety
Keywords: rabies; autopsy; biosafety